1996
DOI: 10.1136/jmg.33.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Suggestion of a major gene for familial febrile convulsions mapping to 8q13-21.

Abstract: Febrile convulsions affect 2 to 5% of all children under the age of 5 years. These convulsions probably have a variety of causes, but a genetic component has long been recognised. A large and remarkable family is described in which febrile convulsions appear to result from autosomal dominant inheritance at a single major locus. A gene for febrile convulsions was excluded from regions of previously mapped epilepsy genes and extension of exclusion mapping, using microsatellite markers, to the entire genome impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
2
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 16 publications
2
107
2
5
Order By: Relevance
“…Because the febrile seizure is the most commonly provoked seizure afflicting infants and children, it is likely that numerous factors contribute to generate heterogeneous seizure phenotypes. Actually, several loci are known to be responsible for FS (5)(6)(7)(8)(9). The febrile seizures of mother and maternal aunt may therefore most probably be accounted for by defects in other genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the febrile seizure is the most commonly provoked seizure afflicting infants and children, it is likely that numerous factors contribute to generate heterogeneous seizure phenotypes. Actually, several loci are known to be responsible for FS (5)(6)(7)(8)(9). The febrile seizures of mother and maternal aunt may therefore most probably be accounted for by defects in other genes.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive genetic studies have demonstrated that four loci are responsible for FS: FEB1 at chromosome 8q13-q21; FEB2, 19p; FEB3, 2q23-24; and FEB4, 5q14-q15 (5)(6)(7)(8)(9). A small population of individuals with FS has additional generalized epilepsy (1) or afebrile seizures.…”
Section: Generalized Epilepsy With Febrile Seizures Plus (Gefs؉) a Cmentioning
confidence: 99%
“…Of these patients, two had a MRI-evidenced MTS, but only one (IV-3) showed FS lasting up to 15 min, indicating a putative example of complex FS. The association between familial AD FS and MTLE has already been proposed in large pedigrees, suggesting a common genetic basis whether MTS is present or not (2,15). In particular, it has been shown that a family history of simple FS also can be a risk factor for MTLE (16).…”
Section: Discussionmentioning
confidence: 92%
“…4,15 In addition, linkage studies have identified 7 genomic regions likely to harbor genes increasing risk for GEFSϩ and 5 regions likely to harbor genes increasing risk for FS (table 1). [16][17][18][19][20][21][22][23][24][25][26] Two loci originally described as FS loci (FEB3 and FEB4) were reported in pedigrees best classified as GEFSϩ due to phenotypes beyond typical FS. 20,21,27 Here we describe a GEFSϩ kindred from Central America with evidence for linkage to chromosome 6q16.…”
mentioning
confidence: 99%